Body composition and menstrual cycle in endurance-trained females: A pilot study - Delgado, B.; Castro, E. A.; Cupeiro, R.; Barba, L.; Barrionuevo, E.; Peinado, A. B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The association between menstrual cycle and body composition (BC) in healthy sedentary women has been widely studied (Elliot et al., 2015; Marsh and Jenkins, 2002); however, few studies have evaluated the relation between the different menstrual cycle phases and BC in athletes (Wojtys et al., 2015). Therefore, the aim of this study was to assess the influence of the menstrual cycle phases on BC variables in endurance-trained females. Methods: Six endurance-trained females (body mass index 18.4 kg/m2); aged 36.67±4.46 years, participated in this study. BC variables were measured by bioelectrical impedance (OMRON BF 306W analyzer, OMRON HEALTHCARE Co., Ltd, Ukyo-ku, Kyoto, Japan), at three phases of the menstrual cycle: Early Follicular Phase, (EFP), Midfollicular Phase (MFP) and Luteal Phase (LP). One-way ANOVAs with repeated measures were used to analyze differences among menstrual cycle phases and BC variables. Results: No significant differences were observed for body weight, fat mass and lean body mass percentages, water or impedance among phases (p>0.05). Discussion: Differences between menstrual and follicular phases for weight and fat free mass, as well as between the follicular and luteal phase for weight, has already been reported for sedentary women (Gleichauf and Roe, 1989). However, our results did not show differences in BC throughout the cycle in trained females. Although our data are preliminary, our outcomes are in agreement with other findings in female athletes (Marsh and Jenkins, 2002; Teixeira et al., 2013). Suggesting a different BC behaviour throughout the menstrual cycle in trained women compared with healthy non-athlete females. More data are needed in order to elucidate the specific interaction between sex hormones changes and BC variables when studying endurance-trained women.